The nutritive value of forage legume crop residues and native pasture in southern Ethiopia - Migongo-Bake, W. (1986)
Presents data on the nutritive value of residues from three legume crops, viz. Cajanus cajan, Lablab purpureus and Vigna unguiculata, grown in southern Ethiopia; compares findings with those for native grasses.